The Northern home front during the Civil War - Cimbala, Paul A. (Paul Alan), 1951-; Miller, Randall M. (North's Civil War., 2023)
With a new preface and updated historiographical essay. Based on recent scholarship and deep research in primary sources, especially the letters and diaries of "ordinary people," The Northern Home Front during the Civil War is the first full narrative history and analysis of the northern home front in almost a quarter-century. It examines the mobilization, recruitment, management, politics, costs, and experience of war from the perspective of the home front, with special attention to the ways the war affected the ideas, identities, interests, and issues shaping people's lives, and vice versa. The book looks closely at people's responses to war's demands, whether in supporting the Union cause or opposing it, and it measures the ways the war transformed society and economy or simply reconfirmed ideas and reinforced practices already underway. As The Northern Home Front during the Civil War reveals, issues and concerns of emancipation, conscription, civil liberties, economic policies and practices, religion, party politics, war management, popular culture, and work were all part of what Lincoln rightly termed "a People's Contest" and as much as the armies in the field determined the outcome of the nation's ordeal by fire. As The Northern Home Front during the Civil War shows, understanding the experience of the women and men on the home front is essential to realizing Walt Whitman's oft-"ed call to get "the real war" into the books.